Design and Implementation of A Smart Home System With The Internet of Things (IoT) Using Esp32 - Abdul Kholik, Moh; Fajar Budi Setiawan; Arma Fauzi (Pusat Penelitian dan Pengabdian Pada Masyarakat Sekolah Tinggi Manajemen Informatika dan Komputer AKBA Makassar, 2023)
This Internet of Things technology is created and developed by humans to facilitate every work and affairs in various aspects of life. One of them can be applied in everyday life. The day is controlling household electrical appliances to turn off and on from loot. The use communication Internet through Android smartphones. The tool needed a device ESP32 as the intermediary to connect the instrument to network the Internet to Android smartphones. This study built the system using a microcontroller working with relays. In this system, the relay acts as a switch for turning off and on the device. Electricity Action: Turning off and turning on electrical equipment remotely. Generated tools in the form of controlling Android-based lights using ESP32 technology and can use Smartphones and Android to control the lights.